Chronic Administration of Δ9-Tetrahydrocannabinol Alters Brain Glucose Uptake and Improves Waiting Impulsivity in the Rat. - Miederer, Isabelle; Schmitt, Ulrich; Bausbacher, Nicole; Röhrich, Jörg; Mildenberger, Philipp; Lutz, Beat; Tüscher, Oliver; Schreckenberger, Mathias (Cannabis & Cannabinoid Research, 2024)
Introduction: Δ9-Tetrahydrocannabinol (THC) acts as an agonist at cannabinoid receptors. Its chronic intake affects many behaviors, including cognitive processes. The aims of this study in rats are to assess the chronic effects of THC on impulsivity and on regional brain glucose uptake. Materials and Methods: For the determination of "waiting impulsivity," a total of 20 male Lister Hooded rats were trained to perform a reaction time task, followed by a baseline test of impulsivity and baseline glucose uptake measurements with [18F]-fluoro-2-deoxy-D-glucose and positron emission tomography (PET). Then, 10 rats each received 3 mg/kg THC or vehicle injected intraperitoneally daily for 21 days. Subsequently, a second behavioral test and PET measurements were performed, and blood THC concentrations were determined. Analyses of variance of brain regions of the impulsivity network with the parameter "standardized uptake value" regarding glucose uptake and correlation analyses of the collected parameters were carried out. Discussion: After chronic THC treatment, decreased glucose uptake (p-values <0.05) was found in cingulate cortex, hippocampus, amygdala, thalamus, and cerebellar cortex, as compared with vehicle-treated rats. The number of correct no-go responses (increased waiting time) significantly increased (p<0.05) in THC-treated rats. Furthermore, correct no-go responses correlated positively and strongly with the THC blood concentrations (Spearman's ρ=0.79, p<0.01). Conclusion: These findings reflect a specific reduction in impulsive behavior after chronic THC treatment, showing a functionally relevant influence of THC on "waiting impulsivity" with reduced selective glucose uptake at the same time.